The barite record of the past seawater oxygen isotope composition - Tao Han; Huiming Bao; Yongbo Peng; Zhitong Lu; Yunzhou Song (Nature Communications)
Abstract The oxygen isotope composition of seawater (δ18Oseawater) is shaped by high- and low-temperature rock-water interactions, reflecting Earth system’s dynamics and evolution. The history of δ18Oseawater remains debated due partly to post-depositional imprints to all current mineral proxies. The oxygen atoms in sulfate minerals are among the most inaccessible to later exchange but often not in isotope equilibrium with ambient water. However, the δ18Osulfate may reach a plateau or approach equilibrium with the δ18Oseawater as the corresponding δ34Ssulfate increases during microbial sulfate reduction. Here we show 289 paired δ18O-δ34S values for sedimentary barite spanning six periods of the Phanerozoic Eon. The δ18O-δ34S trajectories point to variable equilibrium δ18Obarite values for different periods. A ~ 4‰ lower δ18Oseawater value is evident before the Carboniferous than today if assuming the same formation temperature. Utilizing the barite δ18O-δ34S trajectory approach, we now have a robust proxy to advance the long-debated issue of seawater δ18O history.